Reproductive performance in sows in relation to Japanese Encephalitis Virus seropositivity in an endemic area - Lindahl, Johanna (Springer Netherlands, 2011)
Japanese Encephalitis Virus (JEV) is considered an important reproductive pathogen in pigs. Most studies of the reproductive impact of JEV have been conducted in areas where the disease occurs in seasonal epidemics. In this study, the associations between seropositivity for JEV, measured with an IgG ELISA, and the number of piglets born alive and stillborn were investigated in a tropical area endemic for JEV in Vietnam. Sixty percent of sows from four farms in the Mekong delta of Vietnam were seropositive to JEV and the Odds Ratio for a sow being infected was highest (6.4) in sows above 3.5 years (95% confidence interval 2.2–18.3). There was an association between increasing Optical Density (OD) values from the ELISA and the number of stillborn piglets in sows less than 1.5 years, but no effect of seropositivity could be shown when all sows were studied. OD values had an effect (p = 0.04) on the number of piglets born alive in the statistical analysis only when interacting with the effect of the breeds. An increase in mean OD value of the herd was correlated (p < 0.0001) with an increase in the number of piglets born alive. In this study, there was evidence of a negative association between seropositivity for JEV and the reproductive performance only in sows less than 1.5 years in endemic areas. This could be explained by a year-round infection with the virus, which would lead to immunity in many gilts before their first pregnancy. This, in turn, may imply that JEV infection in pigs is of minor importance for the reproductive performance in endemic areas.